Impact of Global Climate Shifts on the Biodiversity and Functionality of Marine Zooplankton Communities - Angkasa Putra; Sarifah Aini; Hamdani; Cici Maulida; Lalu Achmad Jani Qhadaffi; Monica Ryan; Harminto; Made Ariana; Raedy Anwar Subiantoro; Tashwir (Journal of Tropical Biodiversity and Biotechnology, 2025)
The impact of climate change is one of the biggest crises facing humanity today. Not only humans are affected, but also the conditions of the marine environment, including zooplankton communities, which are a key component in the marine food chain. This study reviews the analysis of the impact of global climate shifts on biodiversity and the function of marine zooplankton communities. Specifically, the study addresses how temperature changes, ocean acidification, and other stressors affect zooplankton communities. In addition, the study includes an analysis of case studies and regional variations on the impacts of climate change on zooplankton communities, as well as discusses methodologies that can be used in studying the effects of climate change. We also evaluate existing knowledge gaps and identify future research directions that are needed. Through this latest evaluation, the research highlights the importance of continuous monitoring and a multi-stressor research approach. The study also emphasizes the importance of designing effective adaptation strategies for marine zooplankton communities, which are highly relevant to future sustainable marine conservation policies. The results of this study show the urgency of further research to maintain the integrity of marine ecosystems in facing the challenge of global climate change.